GUIDELINES FOR TEACHING FOREIGN_LANGUAGE MINING TERMINOLOGY USING COMMUNICATIVE AND COGNITIVE TECHNIQUES - Niyozova Yulduz Tashmuradovna (Bright Mind Publishing, 2025)
In order to build future mining engineers' professional-oriented communicative ability, teaching mining terminology is a crucial duty. The principles of using a communicative-cognitive strategy to teach foreign-language mining terminology are examined in this article. This article discusses the general didactic, particular methodological, and linguistic-methodological concepts that underpin the use of a communicative-cognitive approach to teaching foreign language terminology to mining students.
Keywords: Communicative approach, cognitive approach, mining terminology, speech activity, didactics, English for professional reasons, and foreign language teaching concepts.